The Emotion Regulation Questionnaire in Women with Cancer: A Psychometric Evaluation and an Item Response Theory Analysis - Brandão, Tânia (2018)
Objective: Emotion regulation is thought to play an important role in adaptation to cancer. However, the Emotion Regulation Questionnaire (ERQ), a widely-used instrument to assess emotion regulation, has not yet been validated in this context. This study addresses this gap by examining the psychometric properties of the ERQ in a sample of Portuguese women with cancer. Methods: The ERQ was administered to 204 women with cancer (M age = 48.89 years, SD = 7.55). Confirmatory factor analysis (CFA) and item response theory (IRT) analysis were used to examine psychometric properties of the ERQ. Results: CFA confirmed the two-factor solution proposed by the original authors (expressive suppression (ES) and cognitive reappraisal (CR)). This solution was invariant across age and type of cancer. IRT analyses showed that all items were moderately to highly discriminant and that items are better suited for identifying moderate levels of ES and CR. Support was found for the internal consistency and test-retest reliability of the ERQ. The pattern of relationships with emotional control, alexithymia, emotional self-efficacy, attachment, and quality of life provided evidence of the convergent and concurrent validity for both dimensions of the ERQ. Conclusion: Overall, the ERQ is a psychometrically sound approach for assessing emotion regulation strategies in the oncological context. Clinical implications are discussed.